The Effect of Naringin on the Apoptosis of Degenerative Nucleus Pulposus Cells: A Study on the Function and Mechanism - Yuan Z; Yang Z (Dove Medical Press, 2022)
Zhenzhen Yuan,* Zhao Yang* Orthopaedics, Tianjin Hospital, Tianjin, People's Republic of China*These authors contributed equally to this workCorrespondence: Zhao Yang, Email anny.allan@126.comObjective: The aim of this study was to explore the naringin suppressive effect on human degenerative nucleus pulposus cells (D-NPCs) apoptosis and its mechanism.Methods: The degenerative NPCs were divided into 5 groups: the blank control (0μg/mL naringin), 10μg/mL, 20μg/mL, 40μg/mL and 100μg/mL naringin group. Flow cytometry and CCK-8 assay were used to determine the influence on the cell apoptosis and viability in the presence of naringin among groups. The expressions of genes and proteins related to apoptosis and ECM were detected, respectively. Finally, the inhibitors or agonist of apoptotic pathways were used for experiments.Results: In this study, we found naringin treatment led to a decrease of the D-NPCs apoptosis at an optimal concentration of 20μg/mL. After naringin treatment, the expressions of Wnt1 and β-catenin; Fas and Fasl; ATF-4 and CHOP; cleaved caspase-3 and caspase-8; P53 and P16INK4a; pro-apoptotic protein Bax were down‐regulated, while the expressions of anti-apoptotic protein Bcl-2, aggrecan and collagen II were up‐regulated in human D-NPCs. The inhibitors or agonist of pathways could promote or reverse the decrease of apoptosis of degenerative NPCs induced by naringin.Conclusion: Our data indicated that naringin had an antiapoptotic effect via inhibiting P53, P16INK4a, Wnt/β-catenin, and related apoptosis pathway, while the expression of ECM was increased in degenerative NPCs.Keywords: apoptosis, naringin, nucleus pulposus cells